Novel hydrolytic extremely halotolerant alkaliphiles from mature landfill leachate with key involvement in maturation process. Issue 1 (2nd January 2017) - Remmas, Nikolaos; Melidis, Paraschos; Voltsi, Chrysoula; Athanasiou, Despoina; Ntougias, Spyridon
ABSTRACT: Mature landfill leachate is a heavily-polluted wastewater due to its recalcitrant nature of organic matter, and high ammonia and salt content. Despite the moderate saline and alkaline nature of this habitat, no attention has been paid to the isolation and functional role of extremophiles in such environment. In this work, a total of 73 and 29 bacterial strains were isolated by using alkaline and saline media, respectively, while bacteria from mature landfill leachate growing in these media were enumerated as 1.5 ± 0.1 (×10 8 ) and 5.8 ± 0.9 (×10 8 ) cfu/L. Based on their pH and salt ranges and optima for growth, all bacterial isolates were halotolerant alkaliphiles (either facultative or obligate), with the majority of them being extremely halotolerant bacteria. These halotolerant alkaliphiles were classified into 14 operational taxonomic units (OTUs). Of these, 12 are placed within known halophilic and alkaliphilic species of the genera Dietzia, Glycocaulis, Halomonas, Marinobacter, Piscibacillus and Rhodobacter, while the remaining OTUs represented two novel phylogenetic linkages among the families Cyclobacteriaceae and Rhodobacteraceae . Examination of their hydrolytic ability through the performance of lipase, protease and β-glucosidase assays using landfill leachate as the growth substrate revealed that all halotolerant alkaliphiles isolated exhibited extremely high lipolytic activities (up to 78, 800 U g −1 protein), indicating a key involvement of extremophilic microbiota at the late landfill maturation stage. The wide extremely lipolytic halotolerant alkaliphilic community identified also makes mature landfill leachate an ideal microbial pool for the isolation of novel extremophiles of biotechnological interest.